Thymoma and Autoimmune Encephalitis: Clinical Manifestations and Antibodies. Issue 5 (September 2021) - Guasp, Mar; Landa, Jon; Martinez-Hernandez, Eugenia; Sabater, Lidia; Iizuka, Takahiro; Simabukuro, Mateus; Nakamura, Masataka; Kinoshita, Makoto; Kurihara, Masanori; Kaida, Kenichi; Bruna, Jordi; Kapetanovic, Solange; et al.
Abstract : Objective: To report the clinical, neuroimaging, and antibody associations in patients with autoimmune encephalitis (AE) and thymoma. Methods: A retrospective cohort study of 43 patients was conducted. Antibody determination and immunoprecipitation to characterize novel antigens were performed using reported techniques. Results: Patients' median age was 52 years (range: 23–88 years). Forty (93%) had neuronal surface antibodies: gamma-aminobutyric acid receptor A (GABAA R) (15), amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) (13), contactin-associated protein-like 2 (CASPR2) (4), leucine-rich, glioma inactivated 1 (LGI1) (3), glycine receptor (GlyR) (3), and unknown antigens (2). Concurrent antibodies against intracellular antigens occurred in 13 (30%; 9 anti–collapsin response mediator protein 5 [CRMP5]) and were more frequent in anti-AMPAR encephalitis (54% vs 20%; p = 0.037). The most common clinical presentation was encephalitis with multiple T2/fluid-attenuated inversion recovery hyperintense lesions in 23 (53%) patients (15 GABAA R, 5 AMPAR, and 1 unknown neuropil antibody), followed by encephalitis with peripheral nerve hyperexcitability in 7 (16%; 4 CASPR2, 2 LGI1, and 1 unknown antibody), limbic encephalitis in 6 (14%; 4 AMPAR, 1 LGI1, and 1 antibody negative), progressive encephalomyelitis with rigidity and myoclonus in 4 (9%; 3 GlyR and 1 AMPAR antibodies), and encephalitis with normal MRI in 3 (7%; AMPAR antibodies). Anti-GABAA R encephalitis was more prevalent in Japanese patients compared with Caucasians and other ethnicities (61% vs 16%; p = 0.003). In anti-AMPAR encephalitis, 3/4 patients with poor and 0/6 with good outcome had concurrent CRMP5 antibodies ( p = 0.033). Immunoprecipitation studies identified metabotropic glutamate receptor 3 antibodies that were additionally found in 5 patients (3 with and 2 without encephalitis). Conclusions: AE in patients with thymoma include several clinical-radiologic syndromes that vary according to the associated antibodies. Anti-GABAA R encephalitis was the most frequent AE and occurred more frequently in Japanese patients.